The transition radiation detector for ALICE at the LHC - Oyama, Ken (Nuclear instruments & methods in physics research. Section A, Accelerators, spectrometers, detectors and associated equipment, 2010)
The Transition Radiation Detector for the ALICE experiment at the LHC has been developed. It is designed to perform electron identification and on-line tracking of charged particles in the challenging high multiplicity environment of heavy-ion collisions. Thus excellent position resolution and pion rejection capability are required. The design of the detector and its electronics, the status of the project, and results of the commissioning using cosmic rays are presented.